EVALUASI KINERJA PEMASOK DI PT XYZ DENGAN MENGGUNAKAN METODE GABUNGAN PURCHASING PORTOFOLIO MATRIX (PPM) DAN SUPPLIER POTENTIAL MATRIX (SPM) - Satria Bagus Aji; Siti Rahayu; Tri Ngudi Wiyatno (G-Tech: Jurnal Teknologi Terapan, 2025)
The FMCG manufacturing industry faces complex challenges in the supply chain, where supplier performance evaluation is a crucial factor in maintaining production continuity. PT XYZ currently conducts supplier evaluations in a general manner without considering specific segmentation, making it less effective in identifying strategic suppliers and managing risks. The Purchasing portfolio matrix classifies raw materials into strategic, leverage, bottleneck and non-critical groups based on supply risk and profit impact. Meanwhile, the Supplier Potential Matrix (SPM) adds the dimensions of supplier capability and willingness in innovation and collaboration. The combination of these two methods can enhance the effectiveness of supplier evaluation, support procurement strategies, and ensure more optimal business relationships. The weighting of each criterion will be carried out using the Best-Worst Method. Next, the scoring process is conducted based on 13 agreed criteria for each evaluated supplier, totaling 148 suppliers. The results of data processing will be used for segmentation using a hybrid PPM-SPM model. Recommendations are provided for selecting the appropriate supplier relationship management strategy for each supplier segment.